Simulation of Harmonic Impact on Household Electrical Installations Due to the Use of Modern Electronic Equipment - Yosua Mordhekai Hutabarat; Ahmad Rofii (Newinera Publisher, 2025)
The advancement of digital technology has led to increased usage of modern electronic devices in households such as LED televisions, inverter air conditioners, and SMPS-based chargers which are technically classified as non-linear loads. These loads generate harmonics, i.e., waveform distortions of current and voltage due to frequency components other than 50 Hz, which degrade power quality. This study aims to analyze the characteristics and impact of harmonics on household electrical installations and to evaluate the effectiveness of harmonic filters in reducing such distortions. The methodology includes literature review and simulation of a 220 V single-phase residential power system using MATLAB/Simulink. Simulations were conducted under three conditions: linear load usage, non-linear load without filter, and non-linear load with passive LC harmonic filter. Results show that the Total Harmonic Distortion of current (THDi) significantly increased from approximately 0.5% under linear load to 60–70% under non-linear load without filtering, and then dropped to 22–28% with the implementation of LC filter. Power factor also improved from 0.77 to 0.93. The simulation confirms that harmonics severely affect energy efficiency and system stability, and that applying harmonic filters can be an effective mitigation strategy for modern household electrical systems.